2011
DOI: 10.1111/j.1552-6569.2009.00404.x
|View full text |Cite
|
Sign up to set email alerts
|

Rosai-Dorfman Disease with Massive Intracranial Involvement: Asymmetric Response to Conservative Therapy

Abstract: Rosai-Dorfman Disease (RDD) is a rare, idiopathic lymphoproliferative disorder. Central nervous system (CNS) involvement in this disorder is an uncommon manifestation. The clinical and radiographic appearance of CNS RDD is variable, and may mimic more common diseases. Treatment is controversial, and spontaneous remission is common. Positive outcomes have been reported with radiation therapy, or corticosteroid administration, or surgical excision. Our case is unusual in that the extracranial sites of involvemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…12,13 Owing to the location of the lesions complete excision of both lesions was not possible in our case. 12,13 Owing to the location of the lesions complete excision of both lesions was not possible in our case.…”
Section: Discussionmentioning
confidence: 87%
“…12,13 Owing to the location of the lesions complete excision of both lesions was not possible in our case. 12,13 Owing to the location of the lesions complete excision of both lesions was not possible in our case.…”
Section: Discussionmentioning
confidence: 87%
“…Extranodal involvement is observed in approximately 40% of patients diagnosed with RDD, but CNS involvement is very uncommon, with 210 cases reported in the English medical literature, including our 6 patients (Table 2 ). 1 , 3 – 46 , 48 77 , 79 82 , 84 , 85 , 87 , 89 91 , 94 113 , 115 127 In 174 of the reported cases, RDD was isolated to the CNS, while in 36 patients it was part of a systemic disseminated disease (see Table 2 ). CNS involvement has been described in both adults and children, with a mean age at presentation of 39 years and a male prevalence (male: female ratio: 1.8: 1.0).…”
Section: Resultsmentioning
confidence: 99%
“…Of interest, there was a case report on a 54 year-old female patient with both intracranial and extracranial sites of RDD involvement that was initially treated with dexamethasone, followed by oral prednisone. Radiologic follow up demonstrated that dermatologic, mediastinal, and retroperitoneal soft tissue masses responded favorably, but intracranial lesions progressed over the course of 9 months [9].…”
Section: Discussionmentioning
confidence: 98%
“…Most commonly, RDD intracranial manifestations are extra-axial and dura-based masses that mimic meningiomas on imaging [3,4,6,7]. Distinguishing RDD from meningomas on imaging is subtle; RDD has low signal intensity on T2-weighted images hypothesized to be due to free radicals released by inflammatory macrophages [9].…”
Section: Discussionmentioning
confidence: 99%